Implementation of High Value Vegetable Eco Packaging: Case Study on Local Agricultural Company in Yogyakarta - Atin Saraswati; Dikky Indrawan; Amzul Rifin (Business Review and Case Studies, 2023)
A study on the implementation of ecopackaging on high-value vegetables at a local company in Yogyakarta has been carried out. The purpose of this study aims to identify ecopackaging that is preferred by consumers and companies, find out the influencing factors and provide recommendations for making decisions. This research using Quality Function Deployment method approach. QFD translates what the customer wants into what the company produces. The packaging that is liked by consumers and can be provided by companies is the product concept of a box model that can accommodate all vegetable commodities as well as high-value vegetable commodities. Factors in making decisions on implementing ecopackaging in these companies include suitability of form, suitability of materials, price, ease of obtaining materials/availability of raw materials, and packaging design. Recommendations for the implementation of environmentally friendly packaging decision making for high value vegetable products in companies using the QFD method are carried out by involving the active role of consumers, product developers and the company including: managing director, marketing, production team and finance team. Where in this process it is concluded that ecopackaging is recommended to use the form of a cardboard box with paper material for all types of high-value vegetable products. This ecopackaging is intended for PT XYZ B2C consumers with a price priority that is willing to pay IDR 0.- to IDR 5000,-. Keywords: eco packaging, quality function deployment, high value vegetables, green marketing, sustainability